Associations Between Air Pollution Exposure and Daily Pediatric Outpatient Visits for Dry Eye Disease: A Time-Series Study in Shenzhen, China - Jingfeng Mu; Jingfeng Mu; Dan Zeng; Jingjie Fan; Meizhou Liu; Meizhou Liu; Shuyuan Yu; Wanfu Ding; Wanfu Ding; Shaochong Zhang; Shaochong Zhang (Frontiers Media S.A., 2021)
Objectives: This study aimed to investigate the associations between air pollution exposure and pediatric outpatient visits for dry eye disease (DED) in Shenzhen, China.Methods: Generalized additive models were utilized to explore the acute effects of air pollution exposure on pediatric outpatient visits for DED.Results: Single-day lag exposures to NO2, O3, PM2.5, and PM10 were associated with DED outpatient visits at lag days 0, 6, 4 and 2. Relative risks (RRs) for DED given a 10-μg/m3 increase in NO2, O3, PM2.5, and PM10 concentrations were 1.062[95% confidence interval (CI) 1.003, 1.123], 1.015(95% CI 1.001, 1.031), 1.052(95% CI 1.001, 1.115), and 1.038 (95% CI 1.002, 1.076), respectively. RR for DED given a 10-μg/m3 increase in NO2 over cumulative lag days 0-1 was 1.075 (95% CI 1.009, 1.147), and RR for DED given a 10-μg/m3 increase in PM10 over cumulative lag days 0-4 was 1.051 (95% CI 1.003, 1.102).Conclusion: The observed associations between air pollution and outpatient visits for DED may provide evidence for policy makers to consider implementing measures to reduce the risk of DED owing to air pollution in China.